Impact of early life adversities on human brain functioning: A coordinate-based meta-analysis. (June 2020) - Kraaijenvanger, E.J.; Pollok, T.M.; Monninger, M.; Kaiser, A.; Brandeis, D.; Banaschewski, T.; Holz, N.E.
Highlights: Early life adversities can have a substantial impact on the developing brain. These neural alterations might embed latent vulnerability to psychopathologies. Convergence was found in the superior frontal gyrus in healthy subjects. Convergence in the amygdala and in the precuneus were found for emotion and memory. Postnatal early adversities showed convergence in the amygdala and the putamen. Abstract: The detrimental impact of early life adversities (ELAs; entailing pre- and postnatal experiences) on the developing brain has been well established. By inducing neural alterations underlying critical human socio-cognitive functions, ELAs may embed latent vulnerability to psychopathologies. However, single neuroimaging studies report conflicting results. Therefore, this coordinate-based meta-analysis aims to identify convergent functional alterations following ELAs. Electronic databases were searched for relevant articles (2001 to June 2019), retrieving 68 eligible studies containing 3685 unique participants. The activation likelihood estimation algorithm was used for analyses according to best-practice guidelines. Whereas pooled analyses did not yield any findings, further homogenizing the experiments revealed significant functional alterations in the left superior frontal gyrus in healthy subjects, left centromedial amygdala during emotion processing, left precuneus during memory processing and left centromedial amygdala and putamen when analyzing the impact of postnatal experiences. These results support the current consensus in the field of environmental imaging: ELAs might exert their effects through systematically altering critical neurocognitive systems and enhance one's vulnerability to future mental health problems.